2008
DOI: 10.1212/01.wnl.0000316799.86917.37
|View full text |Cite
|
Sign up to set email alerts
|

Impact of white matter hyperintensity volume progression on rate of cognitive and motor decline

Abstract: Background: White matter hyperintensity (WMH) change on brain MRI is observed with increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
222
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(250 citation statements)
references
References 33 publications
(36 reference statements)
25
222
2
1
Order By: Relevance
“…A systematic review revealed that WML affected physical function and elevated fall risk (Zheng et al 2011). Our study also supports other studies showing that WML were associated with gait variables (Bolandzadeh et al 2014;Murray et al 2010;Rosano et al 2010;Silbert et al 2008). Furthermore, WML induced deficits in dual-task performance and elevated the risk of falling (Zheng et al 2012a;Zheng et al 2012b).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A systematic review revealed that WML affected physical function and elevated fall risk (Zheng et al 2011). Our study also supports other studies showing that WML were associated with gait variables (Bolandzadeh et al 2014;Murray et al 2010;Rosano et al 2010;Silbert et al 2008). Furthermore, WML induced deficits in dual-task performance and elevated the risk of falling (Zheng et al 2012a;Zheng et al 2012b).…”
Section: Discussionsupporting
confidence: 88%
“…Structural changes in the aging brain are related to gait performance (for reviews, see Holtzer et al 2014a;Seidler et al 2010). In particular, white matter hyperintensities or lesions (WMLs) have been linked to deficits in physical function among cognitively normal older adults (Bolandzadeh et al 2014;Murray et al 2010;Rosano et al 2010;Silbert et al 2008). WMLs were also shown to affect dual-task performance requiring executive function but not gait task among cognitively normal older adults (Zheng et al 2012a).…”
mentioning
confidence: 99%
“…Longitudinal studies consistently reported a relationship between WML progression and decline in global as well as specific cognitive performance. 10,18,23,24,26,29,[39][40][41][42][43][44][45] In the Cardiovascular Health Study, increase in WML grades was related to global cognitive decline. 24 In the Rotterdam Study, progression of periventricular WMLs was associated with decline in general cognitive performance and information processing speed.…”
Section: White Matter Lesionsmentioning
confidence: 99%
“…Studies that did not compare subjects based on cognitive status Subcortical vs. periventricular WML Five studies [24][25][26][27][28] -four cross-sectional studies and one prospective study -compared the association of subcortical versus periventricular WMLs with cognitive function. In the first cross-sectional study of 1077 older adults [24], WMLs were defined as T2 and PD hyperintensities that were not T1 hypointensities.…”
Section: Overview Of Studiesmentioning
confidence: 99%